If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1n = 2 Solving 15 + -1n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1n = 2 + -15 Combine like terms: 15 + -15 = 0 0 + -1n = 2 + -15 -1n = 2 + -15 Combine like terms: 2 + -15 = -13 -1n = -13 Divide each side by '-1'. n = 13 Simplifying n = 13
| 45+1=x | | y-12=22 | | 13(x-9)=15 | | (-20)(4/5) | | 23+p=50 | | 6a^2+30b^2-18b^3a^3= | | 4c+5=6c+1 | | (8x-9x-4)-(4x+3)=4+16 | | -8x+8=16 | | 1/6y=-10 | | x/7=-3/8 | | x+23=67 | | x^2+2x+11=-90 | | Z=9+y | | 9-3(x+7)=4 | | 6d=10+4d | | b^8=96 | | 3x-(-5)=2x-(-6) | | 4a+5=5+2a | | (2+4)*(8-9)= | | 5r-14-14r+9= | | 5(x-2)=-4x-48 | | 1.6=1.5/y | | -.125=4n | | 6(3-3x)=54 | | 3+3(2x+5)=18 | | 2(x+2)=-4(x-1)-24 | | 5/7x=-4/5 | | y+2Y=7 | | x+7.8=14.3 | | 10x+23(x-3)=162 | | 4-4=10y+3-9y |